Photocatalytic degradation of fractionated crude oil: potential application in oil spill remediation. Issue 1 (1st January 2020) - Agyei-Tuffour, Benjamin; Gbogbo, Selassie; Dodoo-Arhin, David; Damoah, Lucas N.W.; Efavi, Johnson K.; Yaya, Abu; Nyankson, Emmanuel
Abstract: The current oil spill remediation strategies are costly and may be toxic to aquatic species and clean-up workers. There is, therefore, the need to look for alternative oil spill remediation strategies that are less costly and non-toxic. This paper presents the potential of TiO2 and its modified form (Fe-TiO2 ) to remediate crude oil fractions under the irradiation of sunlight (UV-Vis), visible (Vis) and ultra-violet (UV) lights. The TiO2 and Fe-TiO2 were synthesized by mild hydrothermal method and characterized with X-ray diffraction (XRD), Ultra-violet-visible spectroscopy (UV-Vis), Diffusion reflectance spectroscopy (DRS), Thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC), and Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDX). The DRS result of Fe-TiO2 showed an enhanced absorption in the visible light region. The estimated optical band gaps were ~3.12 and ~2.9 eV for TiO2 and Fe-TiO2, respectively. The potential application of TiO2 and Fe-TiO2 in oil spill remediation was investigated through photocatalytic degradation of benzene soluble fraction, n-hexane soluble fraction and 1:1 volume by volume methanol/benzene soluble fraction in crude oil. The degraded crude oil fractions were characterized with UV-vis, Fourier Transform Infrared (FTIR) Spectroscopy and Gas Chromatography-Mass Spectrometer (GC-MS). The FTIR and UV-vis results showed that the Fe-TiO2 was more effective in photodegrading the crude oil fractions under sunlight light irradiation than TiO2 . The GC-MS results showed excellent photodegradation of the various crude oil fractions with the formation of new intermediate products. The results from the study show the potential application of TiO2 and Fe-TiO2 in crude oil spills remediation.